2008
DOI: 10.1103/physrevb.78.041304
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics of two-dimensional electrons in a quantum Hall system probed by time-resolved Kerr rotation spectroscopy

Abstract: Time-resolved Kerr rotation spectroscopy under the radio frequency field to depolarize dynamic nuclear polarization reveals the intrinsic spin-relaxation time ͑T 2 ‫ء‬ ͒ and g factor of two-dimensional electrons in a quantum Hall system. Out-of-plane magnetic field increases the spin coherence drastically through the Landau level quantization. T 2 ‫ء‬ is enhanced strongly around odd filling factors where a quantum Hall ferromagnet is formed. Collapse of spin coherence and appearance of an anomalous Kerr signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 23 publications
(26 reference statements)
3
32
1
Order By: Relevance
“…60 Experimental studies can be found in Refs. [642,643]. doped quantum well, the random spin-orbit coupling leads to a spin relaxation rate two orders of magnitude smaller than that due to the averaged one, leading to a spin lifetime of several tens of nanoseconds in GaAs quantum wells [294].…”
Section: Single-particle Theories For Spin Relaxation In (001) Quantumentioning
confidence: 99%
“…60 Experimental studies can be found in Refs. [642,643]. doped quantum well, the random spin-orbit coupling leads to a spin relaxation rate two orders of magnitude smaller than that due to the averaged one, leading to a spin lifetime of several tens of nanoseconds in GaAs quantum wells [294].…”
Section: Single-particle Theories For Spin Relaxation In (001) Quantumentioning
confidence: 99%
“…22(b), T Ã 2 is plotted as a function of B res , exhibiting a maximum T Ã 2 value of 27 ns and an enhancement at several magnetic fields. Such behavior is reminiscent of Shubnikov-de Haas oscillations as a function of B res ; [117][118][119] however, the enhancement does not exactly match the integer filling factors.…”
Section: G Spin Coherence Timementioning
confidence: 99%
“…Given the tiny deviation from the exact value ν = 1, the spin dephasing time decreased by more than an order of magnitude. For reference: the samples investigated in the previous Kerr experiments [11] could not really exhibit collective states as the mobility of the samples µ e ≃ 1×10 6 cm 2 /Vs does not imply the presence of a long-range order QHF. In those works the change of spin relaxation time in transition from the QHF to skyrmion systems demonstrated a tiny change in spin relaxation time from 6 to 4 ns.…”
mentioning
confidence: 97%
“…The most comprehensive concept of spin relaxation was developed for the quantum Hall ferromagnet (QHF), ν = 2n + 1 [9][10][11][12][13], in which the n − 1 low Landau levels at T → 0 are fully occupied and the nth level is filled by spin-up electrons aligned along B. The QHF is in fact a high symmetry system for investigating the influence of many-particle Coulomb interactions on the spin excitation spectrum [3][4][5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation